1961
DOI: 10.1002/pol.1961.1205516213
|View full text |Cite
|
Sign up to set email alerts
|

Properties of polyvinylidene fluoride. Part II. Infrared transmission of normal and thermally decomposed polymer

Abstract: The infrared transmission of the plastic polyvinylidene fluoride has been measured. Normal and thermally decomposed samples were used. Bands yielding information on phase transitions and behavior during pyrolytic decomposition have been observed. The mechanism of thermal degradation is briefly discussed. Absorption coefficients of important bands have been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1962
1962
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…This suggests that the oxidative decomposition of FCS produces the carbon species, in which the sp 3 component increases with the progress of the decomposition process. This is in line with the char formation after cross-linking the decomposing FCS (Wentink et al 1961). Thus, the significant increase in the absorption in the very broad visible light region, observed by UV-Vis DRS (Fig.…”
Section: Raman Spectrasupporting
confidence: 81%
See 1 more Smart Citation
“…This suggests that the oxidative decomposition of FCS produces the carbon species, in which the sp 3 component increases with the progress of the decomposition process. This is in line with the char formation after cross-linking the decomposing FCS (Wentink et al 1961). Thus, the significant increase in the absorption in the very broad visible light region, observed by UV-Vis DRS (Fig.…”
Section: Raman Spectrasupporting
confidence: 81%
“…Wentink et al (1961) have investigated the thermal decomposition processes of PVdF, mainly by infrared spectroscopy and concluded that the decomposition is preceded by the initial detachment of F, leaving conjugated C=C-C bonds, a part of which forms chars by cross-linking. It is interesting to note that the thermal stability of PVdF significantly decreases by the coexistence of clay (Li and Kim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, normal modes for both phases were determined using UreyeBradley type force fields for the potential function which was fit to experimental results [16]. The observation of a temperature-dependent vibrational spectrum of PVDF was made by Wentink et al [17]. Clarification of the origin of the temperature dependency was made by Cortili and Zerbi who identified the conformational differences between the a-and b-phases and identified unique modes in their respective infrared spectra [18].…”
Section: Introductionmentioning
confidence: 99%
“…Together with this strategy they also used the OPIUM code which led to a full reproduction of the structure and NMR and FTIR vibrational frequencies of the α-PVDF phase. With these results, they contributed to the understanding of those mode ambiguities founded experimentally (Makarevich & Nikitin, 1965;Wentink et al, 1961;Cortili & Zerbi, 1967;Kobayashi et al, 1975). In the case of finite models that are treated as molecules (Das et al, 1999), the DFT methodology with ab-initio methods implemented in the Gaussian 94 software package help in geometric structure, vibrational frequency, dipole moment and singlet-triplet energy separation of CH 2 , CHF, CF 2 , CCl 2 and CBr 2 studies, using B3LYP, B3P86 and B3PW91 hybrid density functionals.…”
Section: Molecular Models Commonly Employed In Qccmentioning
confidence: 99%